Reaching Equilibrium in the Market for Obstetricians and Gynecologists - Reyes, Jessica Wolpaw (American Economic Review, 2007)
In the past 30 years, more and more women have become physicians, receiving training that is indistinguishable from that of their male counterparts. This standardization of human capital accumulation, together with the existence of well-defined specialty categories and clear productivity measures, renders the physician labor market well suited to economic analysis of gender discrimination. The literature indicates that gender gaps in income have faded somewhat, but still persist even within medical specialties. Much of this literature, however, uses older data, does not look at trends over time, or does not take appropriate account of medical specialties or shifts in the age and gender composition of physicians. This paper focuses on the specialty of obstetrics and gynecology (ob-gyn) to gain insight into gender discrimination among highly educated men and women and its evolution in the last 20 years. Ob-gyn is an attractive choice for a number of reasons. First, human capital and production can be measured consistently and accurately. Second, the number of women in the specialty has grown dramatically. While only 12 percent of ob-gyns were female in 1980, the share of women in the field reached 22 percent by 1990 and 40 percent by 2005. Third, ob-gyn is a surgical specialty with an arduous training process. Such specialties have been traditionally male dominated, stressful, and challenging (Janet Bickel 2000). Fourth, there may be discrimination in favor of females on the part